Some Common Fixed Point Theorems in Complex Valued b-Metric Spaces - Aiman A. Mukheimer (The Scientific World Journal)
Azam et al. (2011), introduce the notion of complex valued metric spaces and obtained common fixed point result for mappings in the context of complex valued metric spaces. Rao et al. (2013) introduce the notion of complex valued b-metric spaces. In this paper, we generalize the results of Azam et al. (2011), and Bhatt et al. (2011), by improving the conditions of contraction to establish the existence and uniqueness of common fixed point for two self-mappings on complex valued b-metric spaces. Some examples are given to illustrate the main results.